A 29-Year-Old Female with Progressive Myoclonus and Cognitive Decline. (11th April 2013) - Taylor, D.; Haynes, H. R.; Graham, A.; Gerhand, S.; Kurian, K. M.
Abstract : Myoclonic epilepsy with red ragged fibres (MERRF) is a rare mitochondrial disorder presenting with progressive myoclonus, epilepsy, and cognitive decline. Here, the authors present a case of a 29-year-old lady presenting with myoclonus and describe the subsequent investigations that led to a diagnosis of MERRF. In addition, we examine her cognitive decline over a 9-year period, demonstrating a feature commonly seen in mitochondrial cytopathies.